RNA-binding protein SAM68 interacts with endocytic proteins and actin cyto skeleton modulators - Pankivskyi, S.V.; Senchenko, N.V.; Busko, P.B.; Rynditch, A.V. (Доповіді НАН України, 2020)
SAM68 is a nuclear RNA-binding protein involved in the regulation of mRNA processing. SAM68 overexpression is observed in multiple types of cancer. Recently, the possible link between RNA-binding protein SAM68 and scaffold protein ITSN1 has been identified. The aim of the study was to confirm the probability of direct binding bet ween SAM68 and ITSN, analyze the effect of ITSN1 on SAM68-mediated alternative splicing, and identify novel SAM68 partners among endocytic proteins and actin cytoskeleton modulators. The interactions were revealed in pull-down assays using purified recombinant proteins or cell lysates. ITSN1 knockdown in HeLa cells was performed using the shRNA approach. The expression of isoforms produced by alternative splicing was measured using RT-PCR. It was demonstrated that SAM68 directly interacted with ITSN1 in vitro. Next, it was found that ITSN1 knockdown in HeLa cells induced SRSF1 intron 3 retention increasing the expression of the proto-oncogenic isoform of SRSF1 by three times. It was also shown that SH3 domains of AMPH1, BIN1, CTTN1, TKS4, and TKS5 precipitated SAM68 from lysate of 293 cells. As a result, SAM68 directly binds to ITSN1 and interacts with endocytic proteins and actin cytoskeleton modulators, whereas SAM68-mediated splicing in HeLa cells may be regulated by ITSN1. Метою дослідження було підтвердити можливість прямого зв'язування між SAM68 та ITSN1, проаналізувати вплив ITSN1 на SAM68-опосередкований альтернативний сплайсинг і виявити нових партнерів SAM68 з-поміж ендоцитозних білків та модуляторів реорганізації актинового цитоскелета. Взаємодії проаналізовано за допомогою pull-down методик з використанням очищених рекомбінантних білків або лізатів клітин 293. Нокдаун ITSN1 у клітинах лінії HeLa проводили, використовуючи дві шпилькові РНК. Експресію ізоформ, що утворюються в ході альтернативного сплайсингу, проаналізовано за допомогою ПЛР в реальному часі. Показано, що SAM68 прямо взаємодіє з ITSN1 in vitro. Далі виявлено, що нокдаун ITSN1 у клітинах лінії HeLa підвищує рівень збереження інтрону 3 SRSF1 на 50 %, сприяючи експресії протоонкогенної ізоформи SRSF1. Встановлено, що SH3 домени білків AMPH1, BIN1, CTTN1, TKS4 та TKS5 преципітують SAM68 із лізатів клітин 293. SAM68 безпосередньо зв'язується з ITSN1 і взаємодіє з ендоцитозними білками та модуляторами перебудов актинового цитоскелета, а SAM68-опосередкований сплайсинг у клітинах лінії HeLa може регулюватися ITSN1. Целью исследования было подтвердить возможность прямого связывания между SAM68 и ITSN1, проанализировать влияние ITSN1 на SAM68-опосредованный альтернативный сплайсинг и найти новых партнеров SAM68 среди эндоцитозных белков и модуляторов реорганизации актинового цитоскелета. Взаимодействия проанализированы с помощью pull-down методик с использованием очищенных рекомбинантных белков или лизатов клеток 293. Короткие РНК, образующие шпильки, использовали для нокдауна ITSN1 в клетках линии HeLa. Экспрессия изоформ, образующихся в ходе альтернативного сплайсинга, проанализирована с помощью ПЦР в реальном времени. Показано, что SAM68 прямо взаимодействует с ITSN1 in vitro. Далее обнаружено, что нокдаун ITSN1 в клетках линии HeLa повышает уровень сохранения интрона 3 SRSF1 на 50 %, способствуя экспрессии протоонкогенной изоформы SRSF1. Установлено, что SH3 домены белков AMPH1, BIN1, CTTN1, TKS4 и TKS5 преципитируют SAM68 из лизатов клеток 293. SAM68 непосредственно связывается с ITSN1 и взаимодействует с эндоцитозными белками и модуляторами перестроек актинового цитоскелета, а SAM68-опосредованный сплайсинг в клетках линии HeLa может регулироваться ITSN1.